2016
DOI: 10.1016/j.quascirev.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Long-stored soil carbon released by prehistoric land use: Evidence from compound-specific radiocarbon analysis on Soppensee lake sediments

Abstract: Compound-specific radiocarbon (14 C) analyses allow studying the fate of individual biomarkers in ecosystems. In lakes with small catchments, terrestrial biomarkers have the potential to be used for the dating of sediments that lack the traditionally targeted terrestrial macrofossils, if the specific organic compounds are deposited soon after production. On the other hand, if the biomarkers have been stored for a significant amount of time in the soils of the catchment before transported to the lake, their age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 51 publications
(63 reference statements)
2
59
0
Order By: Relevance
“…In order to yield sufficient amounts of carbon for CSRA, both of these investigations generated 14 C ages from pooled biomarker samples of four compounds each, risking mixing of OC from different sources (i.e., terrestrial and aquatic). The down-core study of Gierga et al (2016) in Lake Soppensee (Switzerland), which featured radiocarbon analysis of some individual long-chain n-alkanes, further suggested that the extent of terrestrial soil storage can change over time. In the present investigation, we were able to isolate a greater number of individual homologues for radiocarbon analysis than in previous lacustrine studies, contributing enhanced molecular-isotopic detail and allowing further inference of OC source and transport in a meromictic lake setting.…”
Section: Introductionmentioning
confidence: 99%
“…In order to yield sufficient amounts of carbon for CSRA, both of these investigations generated 14 C ages from pooled biomarker samples of four compounds each, risking mixing of OC from different sources (i.e., terrestrial and aquatic). The down-core study of Gierga et al (2016) in Lake Soppensee (Switzerland), which featured radiocarbon analysis of some individual long-chain n-alkanes, further suggested that the extent of terrestrial soil storage can change over time. In the present investigation, we were able to isolate a greater number of individual homologues for radiocarbon analysis than in previous lacustrine studies, contributing enhanced molecular-isotopic detail and allowing further inference of OC source and transport in a meromictic lake setting.…”
Section: Introductionmentioning
confidence: 99%
“…Lake studies employing this technique (Douglas et al, 2014;Gierga et al, 2016) have documented pre-aging of organic compounds due to long transport and residence times prior to deposition in sedimentary basins. At Castilla, rapid changes in d 13 C alkane values that correlate strongly with d 13 C bulk values indicate a rapid response of the proxy to vegetation change and no apparent pre-aging of organic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…However, compound-specific radiocarbon analyses of marine (Smittenberg et al, 2004(Smittenberg et al, , 2006Drenzek et al, 2007Drenzek et al, , 2009Kusch et al, 2010) and lacustrine (Douglas et al, 2014;Gierga et al, 2016) sediments have indicated significant age offsets, sometimes millennia, between terrestrially-derived organic compounds and the surrounding sedimentary matrix. This 'preaging' of organic compounds is thought to result from a combination of factors including long transport times, enhanced residence times in soil organic carbon pools, remobilization of buried soil organic matter, and the slow breakdown of organic material (Douglas et al, 2014;Gierga et al, 2016). The observation of preaging of organic compounds in some records raises questions about the chronological control for compound-specific proxies and their comparability to other commonly studied proxies such as fossil pollen, foraminifera, and bulk sedimentary isotopic ratios.…”
Section: Introductionmentioning
confidence: 99%
“…The homologue distribution of leaf wax n-alkanes, as well as their stable hydrogen and carbon isotopic composition, are increasingly used to quantitatively reconstruct past changes in vegetation and hydro-climatic conditions from various sediment archives, including lake sediments (Sauer et al, 2001;Schwark et al, 2002;Sachse et al, 2006;Wirth and Sessions, 2016), loess-paleosol sequences (SchĂ€fer et al, 2018;HĂ€ggi et al, 2019), marine sediments (Schefuß et al, 2005) and fluvial sediment sequences (Bliedtner et al, 2018a). However, 15 reconstructions from sediment archives with associated hydrological catchments can be complicated by the fact that sediments and leaf wax n-alkanes transit through the catchment over hundreds to several thousands of years, and thus the timing of their deposition does not necessarily reflect the timing of leaf wax n-alkane formation (Smittenberg et al, 2006;Feng et al, 2013;Douglas et al, 2014;Gierga et al, 2016;Douglas et al, 2018). Resulting age offsets between leaf wax n-alkane formation and deposition will therefore limit any quantitative paleoenvironmental reconstruction .…”
Section: Introductionmentioning
confidence: 99%
“…These different sources of OC and n-alkanes explain the wide range of 14 C-ages that are reported in the literature for riverine transported particulate organic matter (POC) and leaf wax n-alkanes and n-alkanoic acids (Galy and Eglinton, 2011;Marwick et al, 2015;Tao et al, 2015;Schefuß et al, 2016). Age offsets between leaf wax n-alkane formation and deposition in the order of hundreds to thousands of years were mostly reported from lake sediments, and seem to increase throughout the Holocene due to anthropogenically induced soil erosion (Douglas et al, 2014;Gierga et al, 2016). 30 Possibilities to investigate the sources of OC and n-alkanes and to track their way through hydrological catchments have been made possible by the development of the MIni CArbon-DAting System (MICADAS), that is equipped with a hybrid ion source https://doi.org /10.5194/hess-2019-250 Preprint.…”
Section: Introductionmentioning
confidence: 99%